The Effect of Technology-Based Learning on Learning Motivation of Buddhist Sunday School - Anggelitha, Tiara; Widiyanto, Widiyanto; Suryanadi, Juni; Wulandari, Ayu (Journal of Education, Religious, and Instructions (JoERI), 2025)
The purpose of this study is to identify the effect of technology-based learning on the learning motivation of students at Buddha Dharma Jaya Sunday School. The issues faced by children at the Sunday school include a lack of active participation in the monastery, insufficient motivation or encouragement from parents to engage in monastery activities, and a lack of concentration in learning. This research employs a survey method involving 48 respondents who are children from Buddha Dharma Jaya Sunday School at Jina Marga Dipa Vihara in 2024. The results of the data analysis indicate that the learning motivation variable is categorized as high. Through simple linear regression analysis, it was found that technology-based learning has a positive effect on the learning motivation of Sunday school children. These findings suggest that the integration of technology in the learning process can enhance student engagement and motivation, which in turn can contribute to better learning outcomes. This study provides important insights for educators and monastery administrators in designing more effective and engaging learning strategies for children.